2017
DOI: 10.1101/211680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-omics profiling establishes the polypharmacology of FDA Approved CDK4/6 inhibitors and the potential for differential clinical activity

Abstract: Three inhibitors of the cyclin-dependent kinases CDK4/6, palbociclib, ribociclib, and abemaciclib, have emerged as highly promising therapies for the treatment of breast cancer and other solid tumors. These drugs are reported to have similar mechanisms of action although recent data suggest that abemaciclib exhibits distinct single-agent activity and toxicity. We compare their mechanisms of action using biochemical assays, mRNA profiling, mass spectrometry-based phosphoproteomics, and GR-based dose-response as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
2
6
0
1
Order By: Relevance
“…However, while Cdk4,6 inhibitors such as palbociclib have been observed to limit disease progression, the differences in overall survival compared to standard of care are not statistically significant (Finn et al, 2016; Turner et al, 2018). That Cdk4,6 inhibitors have significant off-target activities (Hafner et al, 2017) raises the possibility that these cancer therapies can be improved by a new class of drugs targeting cyclin substrate recognition and helix-based docking.…”
Section: Discussionmentioning
confidence: 99%
“…However, while Cdk4,6 inhibitors such as palbociclib have been observed to limit disease progression, the differences in overall survival compared to standard of care are not statistically significant (Finn et al, 2016; Turner et al, 2018). That Cdk4,6 inhibitors have significant off-target activities (Hafner et al, 2017) raises the possibility that these cancer therapies can be improved by a new class of drugs targeting cyclin substrate recognition and helix-based docking.…”
Section: Discussionmentioning
confidence: 99%
“…Based on interactions of drug and key modules, we found 8 small molecular agents that could target LOI, including Benzamidine, L-Glutamine, Zinc, XL844, AT7519, AT9283, Alvocidib and Nelarabine. A recent study found that AT7519 and Alvocidib, a cyclin-dependent kinase inhibitor, has been shown to have potential for anticancer effects for cancer treatment [28,29,30,31,32]. XL844, a specific inhibitor of Chk1 and Chk2 kinase, has been found to effectively sensitize cancer cells to induce cell cycle arrest [33].…”
Section: Discussionmentioning
confidence: 99%
“…Abemaciclib, by virtue of its functional group, achieves a better steric complementarity in the CDK4/6 ATP cleft compared to palbociclib and ribociclib [ 30 ]. Besides presenting a higher potency toward CDK4 inhibition, abemaciclib, when higher concentration is achieved, shows the least selectivity against CKDs-cyclins complex compared to palbociclib and ribociclib, as additional interactions occur with other redundant CDK isoforms ( Table 1 ) [ 31 , 32 , 33 ]. Hence, abemaciclib conducts its main efficacy effect targeting CDK4, and secondly, with a lower potency, CDK9 and to an even lesser extent CDK6, responsible for suppressing RB1 phosphorylation and the cell cycle arrest in the G1 phase overall [ 2 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This promiscuity toward CDK isoforms often resulted in a jeopardizing inability to discriminate physiological and malignant proliferative processes, inducing severe cytotoxicity (myelosuppression and anemia) [ 36 ]. Through an increased selectivity, new CDKis show less common and severe hematological adverse events [ 31 ]. Gastrointestinal disorders are instead the most frequent adverse events recorded for abemaciclib with higher incidence of nausea and severe diarrhea compared with palbociclib and ribociclib.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation